2022
DOI: 10.1111/1462-2920.15973
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage S6 requires bacterial cellulose for Erwinia amylovora infection

Abstract: Summary Bacteriophages are highly selective in targeting bacteria. This selectivity relies on the specific adsorption of phages to the host cell surface. In this study, a Tn5 transposon mutant library of Erwinia amylovora, the causative agent of fire blight, was screened to identify bacterial receptors required for infection by the podovirus S6. Phage S6 was unable to infect mutants with defects in the bacterial cellulose synthase operon (bcs). The Bcs complex produces and secretes bacterial cellulose, an extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Other studies have also shown that cellulose‐based scaffolds have the aptitude to store phages consistently for extended periods of time, which is necessary for their efficient usage in diagnostic and therapeutic procedures. [ 60,61 ] Therefore, the developed BC‐based scaffolds in the present study could be employed for many other applications.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also shown that cellulose‐based scaffolds have the aptitude to store phages consistently for extended periods of time, which is necessary for their efficient usage in diagnostic and therapeutic procedures. [ 60,61 ] Therefore, the developed BC‐based scaffolds in the present study could be employed for many other applications.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia phage G7C uses LPS as a receptor, although the adsorption apparatus comprises branched tail fibers (gp63.1 and gp66), where the first one contains the SGNH hydrolase domain and deacetylates the LPS [ 54 ]. LPS and outer polysaccharides were shown to serve as a primary receptor for P. parmentieri phage φA38 [ 55 ] and Erwinia amylovora phage S6 [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The phages S6 ( Knecht et al, 2022 ) and M7 (unpublished results) rely on cellulose and the cellulose synthase complex for host cell infection. Cellulose production was monitored and 1430 Y 2 R produced similar amounts of cellulose as the wild type strain (data not shown).…”
Section: Discussionmentioning
confidence: 98%